Physio-chemical conditions and plankton population of two fishponds in Khulna - Chowdhury, Abdullah Harun; Mamun, Abdullah Al (University Journal of Zoology, Rajshahi University, 2007)
Sixteen physico-chemical variables, and the diversity and abundance of phyto- and zooplankton of two fishponds in Khulna University Campus have been studied during October 2003 and September 2004. A total of 25 phytoplankton genera, 7 belonging to Cyanophyceae, 7 to Chlorophyceae, 8 to Bacillario-phyceae and 3 to Euglenophyceae, and 18 zooplankton genera, 4 belonging to Copepoda, 7 to Cladocera and 7 to Rotifera, were recorded. Both ponds were permanently alkaline in nature. The values of TDS, BOD and phosphate, and the current status of plankton population imply that the study ponds were eutrophic in nature.Key words: Fishponds, physico-chemical conditions, plankton population, KhulnaUniv. j. zool. Rajshahi Univ. Vol.25 2006 p.41-44